VD_FINDINFO Jug / 2019 / 67 vom 17. August 2018 - VD Tribunal cantonal (2018)
CONSTATATION DES FAITS, APPRÉCIATION DES PREUVES, FIXATION DE LA PEINE | 40 CP, 41 CP, 47 CP, 10 CPP (CH), 147 CPP (CH), 158 CPP (CH), 68 al. 1 CPP (CH)